Health information systems as suport for public health service governance: A literature review - Nadia Putri Untiami; Tuanku Banang Rabbani Imsyaamru; Acim Heri Iswanto (PT WIM Solusi Prima, 2026)
The management of public health services currenly relies heavily on the integration of digital technology to minimize information fragmentation and support accurate managerial decision-making. This study aims to synthesize national data on the utilization of Health Information Systems (HIS) and evaluate the role of digital maturity in supporting the efficient management of public health service. The research method employs a qualitative approach with a literature review design through a systematic search of the Google Scholar and PubMed databases for literature published over the past 10 years. The results indicate that effective HIS imlementation positively correlates with improved healthcare worker perfomance and accelerated clinical administration, where accurate data can systematically optimize operational workflows. However, challenges were identified in the form of technical system constraits that cause long queues and the potential for increased administrative workload for nurses if the system is not holistically integrated. It is recommended that future EHR development focus on strengthening cross-system interoperability, simplifying reporting variables, and enhancing human resource capacity through continuous training.